Rhetorical and Reviewing Acts of Transformation and Cunning (on a cloudy day) - Brenda Brueggemann; Elizabeth Brewer Olson (Disability Studies Quarterly, 2020)
No abstract available. Corrigendum Correction of: https://doi.org/10.18061/dsq.v40i1.7470 The authors of the editorial introduction entitled "Rhetorical and Reviewing Acts of Transformation and Cunning (on a cloudy day)" [Disability Studies Quarterly Vol. 40, No. 1, 2020] incorrectly cited the publisher for Jay Dolmage's Disability Rhetoric. The correct publisher should read: Syracuse UP. The correction notice is published in Disability Studies Quarterly Vol. 40, No. 2, 2020, https://doi.org/10.18061/dsq.v40i2.7638.